A modified polypropylene material and its preparation method and application

By adding specific flame retardants, light stabilizers and antioxidants to the modified polypropylene material, the problem of brittle, powdered and discolored during long-term use is solved, and excellent anti-thermal oxygen aging and photoaging properties are achieved, which is suitable for the preparation of thin-walled parts.

CN116836505BActive Publication Date: 2025-03-25KINGFA SCI & TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310520525.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-10
Publication Date
2025-03-25
Estimated Expiration
2043-05-10

AI Technical Summary

Technical Problem

Existing modified polypropylene materials are prone to brittle, powder and discolor during long-term use, and have insufficient anti-thermal oxygen aging performance in outdoor environments, making it difficult to meet the high market requirements for the photothermal aging performance of materials.

Method used

By adding bromine flame retardants, synergistic flame retardants, glass fibers, ultraviolet light absorbers, hindered amine compounds and antioxidants to the polypropylene material, the formulation and preparation process of the material are optimized, and the anti-thermal oxygen aging and anti-photoaging properties of the material are improved.

Benefits of technology

The modified polypropylene material has excellent resistance to thermal oxygen aging, photoaging, low discoloration and high impact strength retention rate, which can effectively extend the service life of the material and be suitable for the preparation of thin-walled parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004220670460000031
    Figure BDA0004220670460000031
  • Figure BDA0004220670460000101
    Figure BDA0004220670460000101
  • Figure BDA0004220670460000111
    Figure BDA0004220670460000111
Patent Text Reader

Abstract

The invention discloses a modified polypropylene material and a preparation method and application thereof. The modified polypropylene material comprises the following components by weight: 20-50 parts of polypropylene; 1-3 parts of a compatibilizer; 15-20 parts of a bromine-based flame retardant; 5-10 parts of a synergistic flame retardant; 15-25 parts of glass fiber; 0.1-0.3 parts of an ultraviolet light absorber; 0.3-0.5 parts of a hindered amine compound; 0.1-0.3 parts of a primary antioxidant; 0.1-0.3 parts of an auxiliary antioxidant; 0.2-0.5 parts of an acid absorber; and the pKa value of the hindered amine compound is less than 8.0. The modified polypropylene material provided by the invention has the characteristics of excellent resistance to thermal oxidative aging, light aging and low discoloration, and can be used to prepare thin-walled parts with high requirements for resistance to thermal oxidative aging and light aging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of modified plastics, and in particular to a modified polypropylene material and a preparation method and application thereof. Background Art

[0002] Polypropylene is widely used in automotive interior and exterior decoration, home appliances, electronics and other industries because of its good processing performance and excellent mechanical, physical and chemical properties, as well as its light weight and low price. With the increasing application of polypropylene in home appliances, automobiles, power tools and new energy, and the increasing application of modified materials in outdoor environments, the market has higher and higher requirements for the photothermal aging performance of materials. During long-term use, polypropylene products tend to become brittle, even powdery, and easy to change color, which seriously affects their use and appearance. How to improve the photothermal aging of flame-retardant reinforced modified polypropylene materials and reduce material discoloration has become an urgent problem to be solved in the development of such materials.

[0003] When the glass fiber in glass fiber reinforced polypropylene is surface treated, some of the treatment agents used usually accelerate the aging of polypropylene; on the other hand, in the preparation process of glass fiber reinforced polypropylene materials, compatibilizers are usually added to form a good interface bonding between the glass fiber and the polypropylene resin. These grafted polypropylene compatibilizers have a great conflict with the components of the ordinary antioxidant system, which will further deteriorate the material's resistance to thermal oxidative aging.

[0004] In addition, adding flame retardants will debrominate during the thermal oxidative aging process, accelerate material degradation, and affect the thermal discoloration of the material. Existing patents currently improve the thermal oxidative aging resistance of polypropylene composite materials by adding other types of additives or increasing the content of antioxidants, but they still fail to solve the aging and light aging discoloration problems.

[0005] In addition, the wall thickness of the part will also affect the actual thermal oxidative aging effect. The thinner the wall thickness, the worse the actual thermal oxidative aging resistance of the part. In the automotive and home appliance fields, the wall thickness of the parts is developing towards thin-walled parts with a thickness of about 1.0-1.5 mm. For thin-walled parts with high thermal oxidative aging resistance requirements, conventional antioxidant systems are difficult to achieve ideal results.

[0006] Therefore, how to reduce the wall thickness of glass fiber reinforced polypropylene while improving its resistance to thermal oxidative aging is an urgent problem to be solved. Summary of the invention

[0007] In order to overcome the defects of the prior art, the present invention provides a modified polypropylene material and its preparation method and application. The modified polypropylene material provided by the present invention has the characteristics of excellent resistance to thermal oxidative aging, light aging, low discoloration and high impact strength retention.

[0008] This is achieved specifically through the following technical solutions:

[0009] A modified polypropylene material, comprising the following components in parts by weight:

[0010] Polypropylene 20-50 parts;

[0011] 1-3 parts of compatibilizer;

[0012] 15-20 parts of brominated flame retardant;

[0013] 5-10 parts of synergistic flame retardant;

[0014] Glass fiber 15-25 parts;

[0015] 0.1-0.3 parts of ultraviolet light absorber;

[0016] 0.3-0.5 parts of hindered amine compounds;

[0017] Primary antioxidant 0.1-0.3 parts;

[0018] Auxiliary antioxidant 0.1-0.3 parts;

[0019] Acid absorbent 0.2-0.5 parts;

[0020] The pKa value of the hindered amine compound is less than 8.0.

[0021] The applicant creatively discovered that low-basic hindered amine compounds with a pKa value of less than 8.0 are not easy to react with the acidic substances generated by the flame retardant, thereby avoiding the phenomenon of failure of the light stabilizer. The acid dissociation constant (pKa) is an index representing the inherent properties of a compound having a group represented by formula (I), and it is determined by conventional titration (i.e., a measurement method based on a defined acid dissociation constant).

[0022] Further, the hindered amine compound comprises a compound represented by formula (I) or a derivative thereof, wherein R1 in formula (I) is selected from C1-C22 alkyl or C1-C18 alkoxy; R2, R3, R4, and R5 are independently selected from C1-C22 alkyl, -H, -OH, -CH2CN, C1-C18 alkoxy, C2-C18 alkoxy substituted by -OH, C5-C12 cycloalkyloxy, C3-C6 alkenyl, C3-C6 alkenyloxy, C7-C9 phenylalkyl which is unsubstituted or substituted by 1, 2 or 3 C1-C4 alkyl groups on the phenyl group, or one or more of C1-C8 acyl; R6 is selected from C x H y N y O a , wherein x is from about 1 to about 22, y is from about 3 to about 46, z is from 0 to about 8, a is from 0 to about 8,

[0023]

[0024] Furthermore, the polypropylene is selected from one or more of homopolypropylene, propylene-ethylene block copolymer, propylene-ethylene random copolymer and propylene-1-butene random block.

[0025] Furthermore, the compatibilizer is maleic anhydride grafted polypropylene and / or maleic anhydride grafted ethylene-octene copolymer, wherein the residual amount of maleic anhydride in the compatibilizer is ≤0.3%, preferably maleic anhydride grafted polypropylene with a residual amount of maleic anhydride <0.2%. A small amount of residual maleic anhydride in the compatibilizer is beneficial to improving the heat-oxidative aging resistance and light-aging resistance of the material.

[0026] Furthermore, the brominated flame retardant is one or more of decabromodiphenylethane, decabromodiphenyl ether, brominated styrene, tris(tribromoneopentyl) phosphate, tetrabromobisphenol A-bis(2,3-dibromopropyl) ether, tris(2,3-dibromopropyl) isocyanurate, tetrabromobisphenol S-bis(2,3-dibromopropyl) ether, 1,2-bis(tetrabromophthalimide) ethane, melamine hydrobromide and 1,2-bis(pentabromophenyl) ethane, preferably 1,2-bis(tetrabromophthalimide) ethane.

[0027] Furthermore, the synergistic flame retardant is one or more of antimony trioxide, antimony pentoxide or zinc stannate; most preferably, the synergistic flame retardant is antimony trioxide.

[0028] Furthermore, the ultraviolet light absorber is at least one of a hydroxybenzophenone light stabilizer and a hydroxybenzotriazole light stabilizer, such as 2-hydroxy-4-n-octyloxybenzophenone, 2-(2′-3′,5′-dipentylphenyl)benzotriazole, and the like.

[0029] Further, the primary antioxidant is one or more of tetrakis[β-(3,5-di-tert-butyl 4-hydroxyphenyl) propionate] pentaerythritol ester, tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate, 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl) isocyanurate, ethylene bis(ethylene oxide)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl) propionate] and 3,9-bis[1,1-dimethyl-2-[(3-tert-butyl-4-hydroxy-5-methylphenyl) propionyloxy]ethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane.

[0030] Further, the auxiliary antioxidant is one or more of dilauryl thiodipropionate, distearyl thiodipropionate, pentaerythritol bis(diphosphite) (2,4-tert-butylphenyl) ester, tris(2,4-di-tert-butylphenyl) phosphite or pentaerythritol tetra(3-laurylthiopropionate), preferably the relative molecular weight of the auxiliary antioxidant is greater than 1000, such as pentaerythritol tetra(3-laurylthiopropionate), tetra(3,5-di-tert-butyl-4-hydroxy)phenylpropionic acid pentaerythritol ester. Relative molecular mass refers to the sum of the relative atomic mass (Ar) of each atom in the chemical formula. The addition of an auxiliary antioxidant having a relative molecular weight greater than 1000 is used in conjunction with the primary antioxidant as an anti-aging auxiliary system, greatly prolonging the oxidation induction period and the aging resistance life, and can improve the aging resistance of the material and prolong the service life of the material.

[0031] Specifically, the acid absorbent is one or more of calcium stearate, zinc stearate, stearic acid, magnesium stearate and hydrotalcite.

[0032] The present invention also provides a method for preparing the modified polypropylene material, comprising the following steps:

[0033] S1: Weigh each component according to the ratio, and premix each component except glass fiber to obtain a premix;

[0034] S2: feeding the premix of step S1 from the main feeding port of the extruder, feeding the glass fiber from the fifth zone of the extruder through a side feeding device, and then melt blending and extruding granulation to obtain the modified polypropylene material.

[0035] Furthermore, the extruder is a twin-screw extruder, the screw speed of the twin-screw extruder is 350-600rpm, the temperature of each section of the screw of the twin-screw extruder from the feeding port to the head is preferably 150-160°C in zones one to five, 180-190°C in zones six to ten, 210-230°C in zones eleven to twelve, the die temperature is 210-230°C, and the vacuum degree is lower than 0.1MPa.

[0036] The present invention also provides the use of the modified polypropylene material in the preparation of vehicle and household appliance parts, such as household passenger vehicles, air conditioners, etc.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] Compared with the existing flame retardant enhancement scheme, by controlling the compounding of auxiliary antioxidants with hindered amine compounds with a pKa value of less than 8.0, the thermal oxidation aging resistance of the material is improved, so that it can be used to prepare thin-walled parts. The thermal oxidation degradation of polypropylene is uneven in the beginning and slowly diffuses from these starting points to the surrounding areas. The acceleration of polypropylene oxidation can be attributed to the peracid formed by the oxidation of aldehyde bonds in polypropylene, which is the result of the oxidation of primary oxidation products. However, in the presence of hindered amine compounds, the oxidation of aldehydes is prevented, the oxidation will not be accelerated, the oxidation will not spread, and the acceleration of oxidation is delayed.

[0039] The modified polypropylene material prepared by the invention is made into a sample strip with a thickness of 0.8 mm, and then a powdering time test is carried out at a high temperature of 160 DEG C. The powdering time is measured to be higher than 830 hours; when the thermal oxygen aging color difference test and the xenon lamp aging color difference test are carried out, the color difference of the material before and after the thermal oxygen aging for 500 hours is measured to be 1.4-2.9, and the color difference before and after the xenon lamp aging is measured to be 1.6-2.8; and the 10% powdering impact strength retention rate is between 70-89%. DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] <Preparation of Examples and Comparative Examples>

[0042] The raw materials used in the examples and comparative examples of the present invention are all commercially available, but are not limited to these materials:

[0043] Polypropylene A: homopolymer polypropylene, brand PP MoplenHP500N, purchased from LyondellBasell;

[0044] Polypropylene B: propylene-ethylene block copolymer, brand PP EP300M, purchased from CNOOC Shell Petrochemical Co., Ltd.;

[0045] Brominated flame retardant: 1,2-bis(tetrabromophthalimide)ethane, brand BT-93W, purchased from Albemarle, USA;

[0046] Synergistic flame retardant: antimony trioxide, brand KS-08, purchased from Chenzhou Antimony Industry;

[0047] Glass fiber: brand ECS13-4.5-508A, purchased from Jushi Group Co., Ltd.

[0048] Compatibilizer A: maleic anhydride grafted polypropylene, maleic anhydride residue is 0.1%, brand MKJ01G, purchased from Shanxi Institute of Applied Chemistry;

[0049] Compatibilizer B: maleic anhydride grafted polypropylene, maleic anhydride residual content is 0.2%, brand SCONATPPP9012FA, purchased from BYK Chemical Co., Ltd., Germany;

[0050] Compatibilizer C: maleic anhydride grafted polypropylene, maleic anhydride residual content is 0.4%, brand 1001CN, purchased from Shanghai Zhuangjing Chemical Co., Ltd.;

[0051] Ultraviolet light absorber: hydroxybenzotriazole light stabilizer, brand name UV-531, purchased from Meifeng Chemical Co., Ltd.;

[0052] Hindered amine compound A: reaction product of α-olefin (C20-C24) containing polymer of maleic anhydride and 2,2,6,6-tetramethyl-4-piperidine, pKa=7.5, brand Uvinul5050H, purchased from BASF;

[0053] Hindered amine compound B: poly{[6-[(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl)imino]-1,6-hexanediyl[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}, pKa=8.6, brand 944FDL, purchased from BASF Corporation, Taiwan;

[0054] Hindered amine compound C: bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate, pKa=4.4, brand 123, purchased from BASF Corporation, Taiwan;

[0055] Primary antioxidant: pentaerythritol tetrakis[β-(3,5-di-tert-butyl 4-hydroxyphenyl) propionate, brand name Irganox1010, purchased from BASF, Germany;

[0056] Auxiliary antioxidant A: tris(2,4-di-tert-butylphenyl) phosphite, relative molecular weight 647, brand 168, purchased from BASF, Germany;

[0057] Auxiliary antioxidant B: 3-(dodecylthio) propionic acid-2,2-bis[[3-(dodecylthio)-propionyloxy]methyl]-1,3-propylene glycol ester, relative molecular weight of 1162, brand AO-412S, purchased from ADEKA Co., Ltd.;

[0058] Auxiliary antioxidant C: pentaerythritol tetrakis (3,5-di-tert-butyl-4-hydroxy) phenylpropionate, relative molecular weight of 1177.66, brand 1010, purchased from BASF, Germany;

[0059] Acid absorbent: hydrotalcite, brand DAH-4A-2, purchased from Kyowa Co., Ltd., Japan.

[0060] The preparation methods of the embodiments of the present invention and the comparative examples are as follows:

[0061] S1: According to the ratios in Table 1 and Table 3, weigh and pre-mix the components to obtain a premix;

[0062] S2: The premix of step S1 is put into a twin-screw extruder for melt blending and extrusion granulation to obtain a modified polypropylene material.

[0063] The temperatures of the screws of the twin-screw extruder from the feed port to the die are preferably 150-160°C for zones 1 to 5, 180-190°C for zones 6 to 10, 210-230°C for zones 11 to 12, the die temperature is 210-230°C, the vacuum degree is lower than 0.1MPa, and the screw speed of the twin-screw extruder is 400r / min.

[0064] The term "part(s)" in this specification means "part(s) by weight" unless otherwise specified.

[0065] <Test Standard>

[0066] The performance test standards of the embodiments and comparative examples of the present invention are as follows:

[0067] Maleic anhydride residue:

[0068] (1) Purification of grafted material: Weigh about 4 g of grafted material and add it together with 200 mL of xylene into a 250 mL distillation flask, heat and dissolve, reflux for 8 to 10 h, cool, add acetone and shake well, let it stand and precipitate, filter, and wash with acetone. Put the filtrate into a 90°C oven to dry for 10 h, and cool it for use.

[0069] (2) Weigh about 2g of the purified grafted material, place it in a 250mL distillation flask, add about 80mL of xylene, and heat and reflux for about 20min until the grafted material dissolves. After cooling, add an excess of 0.1mol / L KOH-ethanol standard solution, and heat and reflux for another 6h. After cooling, use phenolphthalein as an indicator and use 0.1mol / L HCl-isopropanol standard solution to back-titrate the excess KOH-ethanol standard solution. Record the amount of excess alkali consumed and the amount of acid neutralized, and calculate the grafting rate according to formula (3):

[0070] G MAH =9.806(V1C1-C2V2) / 2m

[0071] Where:

[0072] G MAH -1g MAH mass fraction on PP graft, %; C1-KOH-ethanol standard solution concentration, mol / L; C2-HCl-isopropanol standard solution concentration, mol / L; V1-the volume of excess KOH-ethanol standard solution added, mL; V2-the volume of HCl-isopropanol standard solution consumed by back titration neutralization alkali, mL; m-the mass of the refined sample of the graft, g.

[0073] (3) Determination of monomer residual rate

[0074] The residual monomer rate in the grafted product is calculated according to formula (4):

[0075] X=(G 总 -G 精 ) / G total × 100% (4)

[0076] Where: X-monomer residual rate, %; G 总 - Grafting rate measured with unrefined grafted material, %; G 精 -Grafting rate measured using the refined grafted material, %.

[0077] Powdering time (hours): According to ASTM D5423-93 (2005), the ventilation frequency is 5-20 times / hour in an oven, the temperature is set at 160°C, the test specimen strip size is: 100mm×100mm×0.80mm, and the time when the surface cracking or powdering area of ​​the square plate reaches 10% is recorded;

[0078] Determination of powdering area percentage: Sisc IAS metallographic analysis software was used for threshold segmentation and area percentage statistics; the percentage of powdering area of ​​each sample was averaged for the collected images;

[0079] Pka test method:

[0080] In a dry 150mL beaker, add approximately 60mL of 0.100mol·L -1 Hexafluoropropanol (use oxalic acid if measuring weak acids with pKa < 2.3), rinse the burette with this solution, and then fill it to 0.00ml. Accurately release a certain volume of solution (49.95mL in this experiment) into another clean and dry 150mL beaker.

[0081] Place the electromagnetic stirrer in the solution, place the beaker on the electromagnetic stirrer, carefully insert the pH electrode calomel electrode into the solution, and connect it to the potentiometer to record the initial pH value.

[0082] Draw a pH-V curve. When starting the titration, record the pH value every time 1 mL of NaOH is added until the slope of the curve approaches 1.0, then change the alkali solution to record the pH value every time 0.20 mL is added until the slope of the curve approaches infinity, which is the end point. Repeat the titration twice to determine the exact end point volume.

[0083] Find the pKa from the curve. From the pH-V curve, you can find the exact value corresponding to the halfway point of the titrant from the titration endpoint. The corresponding pH value is the apparent pKa.

[0084] Thermal oxygen aging color difference: According to ASTM D5423-93 (2005), the temperature of the oven is set at 160°C with a ventilation rate of 5-20 times / hour. The color difference of the color plate before and after thermal oxygen aging for 500 hours is tested using a desktop high-precision spectrophotometer CS-820N. The test sample is a 0.8mm thick strip.

[0085] Xenon lamp aging color difference: Xenon lamp aging was carried out according to the aging conditions of ISO4892-2 (2013) Cycle No. 1. The desktop high-precision spectrophotometer CS-820N was used to test the color difference before and after aging. The test sample was a 0.8mm thick strip.

[0086] Impact strength retention rate (%): The two groups of specimens A and B (the specimens of group B were lagged for 3 days) prepared according to the ISO180-2019 standard were placed in an I oven with a ventilation frequency of 5-20 times / hour as specified in the standard ASTMD5423-93, and the temperature was set to 160°C. When the specimens of group A showed 10% powdering, the impact strength retention rate of the specimens of group B was tested according to ISO180-2019.

[0087] Table 1. Formulations of Examples 1-11

[0088]

[0089] Table 2. Performance test results of Examples 1-11

[0090]

[0091] Table 3. Comparative Examples 1-4 Formula

[0092] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Polypropylene A (parts) 50 50 50 50 Brominated flame retardant (parts) 19 19 19 19 Synergistic flame retardant (parts) 7 7 7 7 Compatibilizer A (parts) 8 0.3 1 1 Glass fiber (parts) 20 20 20 20 UV absorber (parts) 0.3 0.3 0 0.3 Hindered amine compound A (part) 0.3 0.3 0.3 0 Primary antioxidant (parts) 0.3 0.3 0.3 0.3 Auxiliary antioxidant B (part) 0.3 0.3 0.3 0.3 Acid absorbent (part) 0.2 0.2 0.2 0.2

[0093] Table 4. Performance test results of comparative examples 1-4

[0094] Test items Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 0.8mm@160℃ specimen powdering time (hours) 910 1030 835 620 500 hours thermal oxygen aging square plate color difference ΔE 2.5 2.6 3.1 5.5 1000h xenon lamp aging color difference ΔE 3.1 2.9 3.1 4.4 10% powdering impact strength retention rate (%) 64 65 60 52

[0095] Compared with Example 1, in Comparative Examples 1 and 2, the amount of the compatibilizer exceeds the upper limit or the lower limit, which also leads to a decrease in the thermal oxidation aging and light aging resistance of the material, and a significant decrease in the 10% powdering impact strength retention rate;

[0096] Compared with Example 1, Comparative Examples 3 and 4 do not add ultraviolet absorbers or hindered amine compounds, which also have a negative impact on the material's resistance to heat and oxygen aging, light aging, and impact strength retention.

[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A modified polypropylene material, characterized in that: By weight, it includes the following components: Polypropylene 20-50 parts; 1-3 parts of compatibilizer; 15-20 parts of brominated flame retardant; 5-10 parts of synergistic flame retardant; Glass fiber 15-25 parts; 0.1-0.3 parts of ultraviolet light absorber; 0.3-0.5 parts of hindered amine compounds; Primary antioxidant 0.1-0.3 parts; Auxiliary antioxidant 0.1-0.3 parts; Acid absorbent 0.2-0.5 parts; Wherein, the pKa value of the hindered amine compound is less than 8.0; The compatibilizer is maleic anhydride grafted polypropylene and / or maleic anhydride grafted ethylene-octene copolymer; The synergistic flame retardant is one or more of antimony trioxide, antimony pentoxide or zinc stannate; The brominated flame retardant is one or more of decabromodiphenylethane, decabromodiphenyl ether, brominated styrene, tris(tribromoneopentyl) phosphate, tetrabromobisphenol A-bis(2,3-dibromopropyl) ether, tris(2,3-dibromopropyl) isocyanurate, tetrabromobisphenol S-bis(2,3-dibromopropyl) ether, 1,2-bis(tetrabromophthalimide) ethane, melamine hydrobromide and 1,2-bis(pentabromophenyl) ethane; The ultraviolet light absorber is at least one of a hydroxybenzophenone light stabilizer and a hydroxybenzotriazole light stabilizer.

2. The modified polypropylene material according to claim 1, characterized in that: The hindered amine compound comprises a compound represented by formula (I) or a derivative thereof, wherein R1 in formula (I) is selected from C1-C22 alkyl or C1-C18 alkoxy; R2, R3, R4, and R5 are independently selected from C1-C22 alkyl, -H, -OH, -CH2CN, C1-C18 alkoxy, C2-C18 alkoxy substituted by -OH, C5-C12 cycloalkyloxy, C3-C6 alkenyl, C3-C6 alkenyloxy, C7-C9 phenylalkyl which is unsubstituted or substituted by 1, 2 or 3 C1-C4 alkyl groups on the phenyl group, or one or more of C1-C8 acyl; R6 is selected from C x H y N y O a , where x is 1-22, y is 3-46, z is 0-8, a is 0-8, 3. The modified polypropylene material according to claim 1, characterized in that: The polypropylene is selected from one or more of homopolypropylene, propylene-ethylene block copolymer, propylene-ethylene random copolymer and propylene-1-butene random block.

4. The modified polypropylene material according to claim 1, characterized in that: The residual amount of maleic anhydride in the compatibilizer is ≤0.3%.

5. The modified polypropylene material according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polypropylene with a maleic anhydride residue less than 0.2%.

6. The modified polypropylene material according to claim 1, characterized in that: The brominated flame retardant is 1,2-bis(tetrabromophthalimide)ethane.

7. The modified polypropylene material according to claim 1, characterized in that: The primary antioxidant is one or more of tetrakis[β-(3,5-di-tert-butyl 4-hydroxyphenyl) propionate] pentaerythritol ester, tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate, 1,3,5-tris(4-tert-butyl-3-hydroxy-2.6-dimethylbenzyl) isocyanurate, ethylene bis(ethylene oxide)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl) propionate] and 3,9-bis[1,1-dimethyl-2-[(3-tert-butyl-4-hydroxy-5-methylphenyl) propionyloxy]ethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane.

8. The modified polypropylene material according to claim 1, characterized in that: The auxiliary antioxidant is one or more of dilauryl thiodipropionate, distearyl thiodipropionate, pentaerythritol bis(2,4-tert-butylphenyl) diphosphite, tris(2,4-di-tert-butylphenyl) phosphite, 3-(dodecylthio) propionate-2,2-bis[[3-(dodecylthio)-propionyloxy]methyl]-1,3-propylene glycol ester or pentaerythritol tetra(3-laurylthiopropionate), and the relative molecular weight of the auxiliary antioxidant is greater than 1000.

9. The modified polypropylene material according to claim 1, characterized in that: The acid absorbent is one or more of calcium stearate, zinc stearate, stearic acid, magnesium stearate and hydrotalcite.

10. The method for preparing the modified polypropylene material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Weigh each component according to the ratio, and premix each component except glass fiber to obtain a premix; S2: feeding the premix of step S1 from the main feeding port of the extruder, feeding the glass fiber from the fifth zone of the extruder through a side feeding device, and then melt blending and extruding granulation to obtain the modified polypropylene material.

11. Use of the modified polypropylene material according to any one of claims 1 to 9 in the preparation of vehicle and household appliance parts.

Citation Information

Patent Citations

  • Stabilization of polycarbonate / ABS blends with mixtures of hindered amines and UV absorbers

    CA2255459A1

  • Flame-retardant polypropylene compound for sanitary ware product

    CN101759930A